Avaliação das atividades genotóxica, antigenotóxica, citotóxica, anticitotóxica, angiogênica e antiangiogênica de elagitaninos utilizando ensaios in vitro e in vivo - Carneiro, Cristiene Costa (2016)
Punicalagin and gemin D are ellagitannins found in some species of plants of medical importance such as Punica granatum and Geun japonicun. For this study, punicalagin and gemin D were isolated, respectively, from the leaves of Lafoensia pacari and Eugenia uniflora, two species of Brazilian medicinal plants with several biological activities, such as antitumoral, antioxidant and healing of wounds. In the present study, we evaluated the genotoxic, cytotoxic, antigenotoxic and anticytotoxic effects of gemin D using the Ames test in Salmonella typhimurium, the micronucleus (MN) test and comet assay in mice. With the punicalagin ellagitannin, we assessed the same effects mentioned above using the comet and MN tests in mice, and we also evaluated the angiogenic and antiangiogenic activities of this ellagitannin by the chick chorioallantoic membrane (CAM) angiogenic assay. The results obtained with gemin D showed that this tannin did not present genotoxic effect by the Ames and MN tests, however, in the comet assay, the highest dose of gemin D (100 mg/kg) induced increase of breaks in DNA in comparison to the negative control (p < 0.05). In the antigenotoxicity, gemin D protected DNA against the harmful action of 4-nitroquinoline-1-oxide and sodium azide by the Ames test, and also against cyclophosphamide (CPA) in pre- and co-treatment by MN and comet tests in mice, but it did not protect DNA in the post-treatment. The results obtained with punicalagin showed that this tannin exhibited no genotoxic effect by MN test and comet assay in mice. Only the highest dose of punicalagin (50 mg/kg) exhibited significant cytotoxic effect by MN test, and in the co-treatment with CPA, this cytotoxicity was enhanced. Co-treatment, pre-treatment and post-treatment of punicalagin with CPA led to a significant reduction in the number of DNA breaks and in the frequency of CPA-induced MN, indicating antigenotoxic effect. Using the CAM model, punicalagin exhibited angiogenic activity in all concentrations, mainly at the lowest concentration (12.5 µg/µL). Therefore, gemin D and punicalagin exhibited relevant antigenotoxic and cytotoxic effects, which indicate that they may be probables candidates for chemoprevention or for the development of new cancer therapies. In addition, the angiogenic activity presented by punicalagin in this study could contribute for the processes of tissue repairing and wound healing.